Detection and analysis of drought events in Calabria (Southern Italy) - Coscarelli, Roberto; Caloiero, Tommaso; Ferrari, Ennio; Sirangelo, Beniamino (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value="{"1":2,"2":"Drought phenomena are one of the greatest damaging climate events. For this reason it is necessary to detect several drought features such as its intensity, duration, recurrence probability and spatial extent, also in order to alleviate the impacts of droughts. In this study, drought, expressed using the Standardized Precipitation Index (SPI), has been analyzed in a region of southern Italy (Calabria) using a homogenized database for 24 monthly rainfall series in the 1951-2016 period. First, both the short-term (3 months) and the long-term (24 months) SPI were estimated and, in order to identify the worst events, the percentages of rain gauges falling within severe or extreme dry conditions have been evaluated. Then, the occurrence frequencies of severe/extreme droughts have been evaluated for each rain gauge. Finally, possible trends in the SPI values have been detected by means of a new graphical technique, Sen’s method, which allows the trend identification of the low, medium and high values of a series. Results evidenced that, considering the 3-month SPI, the occurrence frequency of severe and extreme drought events increased from the late 1970s to the early 2000. As to what concerns the 12-month SPI, droughts were more frequent throughout the 1980s and the 1990s and at beginning of this century. The trend analysis showed a general reduction in all the values of the SPI, that is a tendency towards heavier droughts and weaker wet periods."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Drought phenomena are one of the greatest damaging climate events. For this reason it is necessary to detect several drought features such as its intensity, duration, recurrence probability and spatial extent, also in order to alleviate the impacts of droughts. In this study, drought, expressed using the Standardized Precipitation Index (SPI), has been analyzed in a region of southern Italy (Calabria) using a homogenized database for 24 monthly rainfall series in the 1951-2016 period. First, both the short-term (3 months) and the long-term (24 months) SPI were estimated and, in order to identify the worst events, the percentages of rain gauges falling within severe or extreme dry conditions have been evaluated. Then, the occurrence frequencies of severe/extreme droughts have been evaluated for each rain gauge. Finally, possible trends in the SPI values have been detected by means of a new graphical technique, Sen’s method, which allows the trend identification of the low, medium and high values of a series. Results evidenced that, considering the 3-month SPI, the occurrence frequency of severe and extreme drought events increased from the late 1970s to the early 2000. As to what concerns the 12-month SPI, droughts were more frequent throughout the 1980s and the 1990s and at beginning of this century. The trend analysis showed a general reduction in all the values of the SPI, that is a tendency towards heavier droughts and weaker wet periods.